EFEKTIVITAS METODE SOROGAN BERBANTUAN TUTOR SEBAYA TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Ahmat Wakit (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
Mathematics learning with sorogan method assisted by peer tutor is learning where students do the exercises in front of the teacher directly, but the students have studied the exercices with their peers before. The aim of this research was to determine the effectiveness of mathematics teaching with sorogan method assisted by peer tutor. The results of this study was mathematics learning with sorogan method assisted peer tutors was effective and there was an increase of understanding the concept in experimental class.Keywords : sorogan, peer tutor, understanding the concept